2016
DOI: 10.1007/s12350-015-0152-1
|View full text |Cite
|
Sign up to set email alerts
|

Left main coronary artery disease: A review of the spectrum of noninvasive diagnostic modalities

Abstract: Medically managed significant left main (LM) stem disease has been considered a determinant of increased cardiac mortality approaching 50% at 3-year follow-up. Despite the clinical significance of LM disease, studies comparing the various diagnostic modalities, especially noninvasive, are sparse. Clinicians, particularly imagers, should be aware of the strengths and weaknesses of existing modalities to diagnose LM disease as integrating many clues (history, symptoms, electrocardiogram, and stress hemodynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Based on their analysis, the authors state that ''…noninvasive detection of significant LM stenosis is critically important given the underlying extent of myocardium at risk''. 1 They also rightfully conclude that all the reviewed noninvasive methodologies have their intrinsic limitations in assessment of extent of LM disease.…”
Section: See Related Article Pp 1411-1429mentioning
confidence: 86%
See 1 more Smart Citation
“…Based on their analysis, the authors state that ''…noninvasive detection of significant LM stenosis is critically important given the underlying extent of myocardium at risk''. 1 They also rightfully conclude that all the reviewed noninvasive methodologies have their intrinsic limitations in assessment of extent of LM disease.…”
Section: See Related Article Pp 1411-1429mentioning
confidence: 86%
“…1 The authors included a total of 102 references covering this important topic and provided several very interesting Figures. I would specifically mention their Figure 9, with the proposed algorithm and suggestions for utilization of multiple diagnostic imaging modalities as well as Table 1, with a summary of diagnostic strengths and weaknesses for the noninvasive diagnostic modalities reviewed in this paper.…”
Section: See Related Article Pp 1411-1429mentioning
confidence: 99%
“…Lung-heart ratios [55% for TI-201 and [44% for Tc-99m tracers, and transient ischemic dilatation (TID) help better detect patients with severe CAD on MPI. 12 However, in the setting of normal MPI, increased TID ratio has a low prevalence and a poor predictive accuracy and should not be considered as a marker of high risk CAD. 13 Multiple studies have shown the importance of identifying a normal limit for functional parameters obtained by GSPECT in different geographic regions and different ethnicities.…”
Section: See Related Article Pp 652-660mentioning
confidence: 99%
“…It is associated with a poor prognosis and has a detrimental effect on the heart [ 5 ]. Cardiac troponin measurements are considered the preferred diagnostic markers of acute myocardial injury [ 6 ].…”
Section: Introductionmentioning
confidence: 99%